2008
DOI: 10.1063/1.3039080
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of the absorption bands of the first electronic transition in liquid H2O and D2O by attenuated total reflectance far-UV spectroscopy

Abstract: Absorption bands of the first electronic transition (X (1)A(1)-->A (1)B(1)) of water (H(2)O) and heavy water (D(2)O) in the liquid state have been directly observed by using a uniquely designed attenuated total reflectance far-ultraviolet (ATR-FUV) spectrometer. Since the ATR geometry reduces the absorbance, the FUV spectra can be obtained over the entire X (1)A(1)-->A (1)B(1) absorption band, including the band maxima. Systematic measurements of the FUV spectra of H(2)O and D(2)O with heating from 10 to 70 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
108
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 40 publications
(52 reference statements)
8
108
1
Order By: Relevance
“…We attribute these differences to the necessary Kramers-Kronig transformations and analysis inherent to these other studies, whereas our transmission measurement is direct. The entire spectrum redshifts linearly with increasing temperature, in agreement with previous predictions 14,15,[30][31][32] , and by 350°C it has shifted by 0.64 eV to lower energy compared to room temperature. The energy of maximum absorbance, E max , steadily decreases by -0.00203 eV°C À 1 (16.4 cm À 1°C À 1 ) ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…We attribute these differences to the necessary Kramers-Kronig transformations and analysis inherent to these other studies, whereas our transmission measurement is direct. The entire spectrum redshifts linearly with increasing temperature, in agreement with previous predictions 14,15,[30][31][32] , and by 350°C it has shifted by 0.64 eV to lower energy compared to room temperature. The energy of maximum absorbance, E max , steadily decreases by -0.00203 eV°C À 1 (16.4 cm À 1°C À 1 ) ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 78%
“…The energy of maximum absorbance, E max , steadily decreases by -0.00203 eV°C À 1 (16.4 cm À 1°C À 1 ) ( Supplementary Fig. 1), also in reasonable agreement with previous experimental approximations 14,15,34 and theoretical predictions 21 . The maximum extinction coefficient steadily decreases linearly (e max ¼ À 0.965T þ 1,598) with increasing temperature, and by 350°C reaches B80% of its roomtemperature value (Supplementary Fig.…”
Section: Resultssupporting
confidence: 75%
“…We have also demonstrated that FUV spectroscopy can be effectively utilized for the quantitative and qualitative analyses of solutes in aqueous solutions because the absorption band near 150 nm due to the first electronic transition (Ã ← X) of liquid water (the ñ → σ* transition of liquid water) is very sensitive to changes in hydrogen bonding. 6,12,13 The foot of this band can be observed in the 190 -210 nm region by using an ordinary UV-Vis spectrometer. We demonstrated the potential of FUV spectroscopy in measuring minute quantities of solutes in aqueous solutions, including aqueous mixtures of NH3 and H2O2.…”
Section: Introductionmentioning
confidence: 99%
“…Using it, we investigated how the (Ã ← X) band of water is affected by the addition of solutes to water. 12,13 We utilized this new technique to monitor the quality of semiconductor wafer cleaning solutions. 8 While the ATR-FUV spectrometer is powerful in that one can observe the whole (Ã ← X) band near 150 nm of water and can investigate effects of hydration on the band, it is often enough to employ an ordinary UV-Vis spectrometer for qualitative and quantitative analysis of various aqueous solutions because one can use the foot near 200 nm of the strong 150 nm band.…”
Section: Introductionmentioning
confidence: 99%
“…Time-resolved photoelectron spectrum of a 30 mM NaCl solution in a) H 2 O and b) D 2 O (7.75 eV pump, 3.10 eV probe). Spectra for given delays are shown in c) for H 2 O and d) for D 2 O. Panel e) shows the time evolution of the average binding energy for the two sample solutions.…”
mentioning
confidence: 99%